Travelling for treatment; does distance and deprivation affect travel for intensity-modulated radiotherapy in the rural setting for head and neck cancer?. Issue 6 (22nd March 2017) - Cosway, B; Douglas, L; Armstrong, N; Robson, A
Abstract: Objective: NHS England has commissioned intensity-modulated radiotherapy for head and neck cancers from Newcastle hospitals for patients in North Cumbria. This study assessed whether travel distances affected the decision to travel to Newcastle (to receive intensity-modulated radiotherapy) or Carlisle (to receive conformal radiotherapy). Methods: All patients for whom the multidisciplinary team recommended intensity-modulated radiotherapy between December 2013 and January 2016 were included. Index of multiple deprivation scores and travel distances were calculated. Patients were also asked why they chose their treating centre. Results: Sixty-nine patients were included in this study. There were no significant differences in travel distance ( p = 0.53) or index of multiple deprivation scores ( p = 0.47) between patients opting for treatment in Carlisle or Newcastle. However, 29 of the 33 patients gave travel distance as their main reason for not travelling for treatment. Conclusion: Quantitatively, travel distance and deprivation does not impact on whether patients accept intensity-modulated radiotherapy. However, patients say distance is a major barrier for access. Future research should explore how to reduce this.